The impact of fluid overload on mortality and acute kidney injury - Md Ralib, Azrina; Pickering, John W.; Shaw, Geoffrey M.; Endre, Zoltan H. (2013)
INTRODUCTION AND AIMS: Aggressive volume resuscitation is often required in critically ill patients to maintain haemodynamic stability and end organ perfusion. There has been growing concern about the adverse effects of positive fluid balance on mortality and acute kidney injury (AKI) incidence. We aimed to investigate the impact of fluid overload on mortality, and on delay in AKI diagnosis and on misclassification of AKI severity in general intensive care unit (ICU) patients. METHODS: We prospectively screened all admissions to a single general ICU for one year. Patients were excluded if they were under 17 years of age, stayed in the ICU for less than 24 hours, or without recorded body weight or data to calculate fluid balance. Fluid input and output, body weight, and plasma creatinine measurements were extracted from clinical records. Fluid accumulation of more than 5% body weight was used to define fluid overload. Plasma creatinine concentration was adjusted for cumulative fluid balance at time of measurement. AKI was defined and classified based on creatinine criteria using the KDIGO (Kidney Disease: Improving Global Outcomes) definition. RESULTS: Of 725 ICU admissions, 245 (38%) had AKI and 192 (26%) had fluid overload within 24 hours. Four-hundred and eleven patients remained in the ICU for at least 48 hours, of whom 49 (12%) had fluid overload. Cumulative fluid overload over 48 hours was independently predictive of hospital and 1-year mortality [Adjusted Odds Ratio of 3.73 (95% Confidence interval: 1.98 to 7.02), and 3.15 (1.72 to 5.76), respectively]. Adjusting plasma creatinine reclassified 40 (8%) No-AKI patients as AKI, and 34 patients as having more severe AKI. Reclassified AKI patients had longer ICU lengths of stay (p<0.02), and were 70% more likely to die in hospital than those not reclassified. CONCLUSIONS: Cumulative fluid overload over 48 hours was independently associated with mortality in a heterogenous group of critically ill patients. Positive fluid balance masked AKI diagnosis or misclassified severity in 74 (10%) of patients, which was associated with increased mortality. Application of a simple formula to correct for plasma creatinine dilution is necessary in patients undergoing volume resuscitation.